Iridoid glucosides from Randia spinosa (Rubiaceae) - Hamerski, Lidilhone [UNESP]; Furlan, Maysa [UNESP]; Siqueira Silva, Dulce Helena [UNESP]; Cavalheiro, Alberto José [UNESP]; Eberlin, Marcos Nogueira; Tomazela, Daniela Maria; Bolzani, Vanderlan da Silva [UNESP] (Elsevier, 2003)
An iridoid glucoside: randinoside, along with five known iridoids: galioside, deacetylasperulosidic acid methyl ester, scandoside methyl ester, geniposide and gardenoside, were isolated from the stems of Randia spinosa. The structures were determined by spectroscopic analysis, including 2D NMR techniques. © 2003 Elsevier Science Ltd. All rights reserved.
Keywords: Iridoid glucosides; Randia spinosa; Rubiaceae; deacetylasperulosidic acid methyl ester; galioside; gardenoside; geniposide; iridoid; plant extract; Randia spinosa extract; randinoside; scandoside methyl ester; unclassified drug; drug isolation; drug structure; medicinal plant; nonhuman; nuclear magnetic resonance; phytochemistry; plant stem; structure analysis; Iridoids; Molecular Structure; Nuclear Magnetic Resonance, Biomolecular; Plant Stems; Spectrometry, Mass, Electrospray Ionization